2011
DOI: 10.5194/acp-11-12067-2011
|View full text |Cite
|
Sign up to set email alerts
|

Fossil versus contemporary sources of fine elemental and organic carbonaceous particulate matter during the DAURE campaign in Northeast Spain

Abstract: We present results from the international field campaign DAURE (Determination of the sources of atmospheric Aerosols in Urban and Rural Environments in the Western Mediterranean), with the objective of apportioning the sources of fine carbonaceous aerosols. Submicron fine particulate matter (PM<sub>1</sub>) samples were collected during February–March 2009 and July 2009 at an urban background site in Barcelona (BCN) and at a forested regional background site in Montseny (MSY). We present radiocarbo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
150
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 165 publications
(186 citation statements)
references
References 91 publications
33
150
3
Order By: Relevance
“…From optical apportionment (Equation (6)), EC resulted mainly of fossil origin in most cases (range 62-87%, except three cases in the range 42-44%), consistent with 14 C studies in the Milan area [40] and in other cities in Europe during wintertime [62,64]. As already found between b abs BrC and levoglucosan, very good correlation was found also between b abs,WB BC and levoglucosan (R 2 = 0.92).…”
Section: Results From the Milan Datasetsupporting
confidence: 68%
“…From optical apportionment (Equation (6)), EC resulted mainly of fossil origin in most cases (range 62-87%, except three cases in the range 42-44%), consistent with 14 C studies in the Milan area [40] and in other cities in Europe during wintertime [62,64]. As already found between b abs BrC and levoglucosan, very good correlation was found also between b abs,WB BC and levoglucosan (R 2 = 0.92).…”
Section: Results From the Milan Datasetsupporting
confidence: 68%
“…In summer, the PM 1 EC f accounted for 90 ± 2% of the total EC at Bern and Moleno, indicating EC is predominantly stemming from road traffic. The high contribution of vehicular emissions to EC was also found in summer in Barcelona (Minguillon et al 2011). EC f and EC bb in the fine size fraction contributed on average 80 ± 5% and 73 ± 14% to the total EC (in PM 10 ) for all sites, respectively.…”
Section: Ec and Oc Concentrationsmentioning
confidence: 76%
“…In the same study, it was found that the fraction of OC attributed to fossil fuel consumption (mainly traffic emissions) was 34 ± 4 % and 31 ± 4 % for winter and summer respectively. Considering the clear seasonality of this source with elevated concentrations in summer, the low contribution of biomass burning to OC concentrations reported by Minguillón et al (2011), the absence of EC in this source and the prohibition of open burning of agricultural biomass during summer (Spanish Decreto 64/1995), it can be reasonably assumed that this source is SOA with negligible input from biomass burning. As observed for the secondary sulphate source, some typical crustal elements such as La, Rb, Ti, Ca, Al, Mg, Fe and Sr are present, for the same reasons already described.…”
Section: Identification Of Emission Sources By Pmfmentioning
confidence: 99%
“…(2) The observed increasing summer trend can be attributed to increased biogenic emissions from local vegetation, and enhanced photochemical reactions (Seco et al, 2012). A study performed by Minguillón et al (2011) reported that the fraction of OC attributed to biomass burning at MSY in winter was 17-21 % and only 12 % in summer. In the same study, it was found that the fraction of OC attributed to fossil fuel consumption (mainly traffic emissions) was 34 ± 4 % and 31 ± 4 % for winter and summer respectively.…”
Section: Identification Of Emission Sources By Pmfmentioning
confidence: 99%
See 1 more Smart Citation